(untitled) (Journal of Engineering, 2002)
The (P.E.) values reveal a similar seasonal variation .for six selected climatological stations 6yr)r Mujib basin’ The average annual values ranges between 2200 mm in the SE region to 1400 mm firr the NW and SW regions of the basin. The relation between the long-te.- uvirug" values and tl e climatic parameters (Class A p*, Temperature; Wind, Sun Shine duration % RH %) for thn e climatological stations were determined using the linear regression equations. High correlatic n coefficient values suggest that the obtained equations are highly reliable. Mujib basin is divided in, o three climatic zones : Moisture index > -80 where the water balance for this zone show, yy4[r)r surplus during Dec. to Feb. and water <ieiicit during March to November. Moisture indexes ranf e between -80 to -90 where the water balance for the normal and wet water years show water surpli.s in lt il zone during the wetted months. Moisture index < -90 where the water deficit is experience d in high degree and no water surplus has been observed.